Vidas em nós: Histórias conectadas com o porto da Raposa, em São João Batista/MA - MARTIN, Manoel de Jesus Barros (2024)
The present work configures itself as a systematic study of the emergence and performance of the port of Raposa, in São João Batista, in the Baixada Maranhense, between the years 1940 and 1980. During this time lapse, such anchorage stood out as the most dynamic among those existing in this region and constituted itself as the connecting link of increasing flows of people and goods in circulation between native production zones and exogenous industrial production zones. Facets of the historical process related to the city of São Vicente Ferrer, from which São João Batista was emancipated, are studied, in whose territory the aforementioned port is located. Representations of regional chroniclers regarding the so-called Baixada do Maranhão are analyzed. A narrative is developed regarding the movement of the port of Raposa and its limits, based on representations drawn from the exegesis of the testimonies of characters who interact with it daily as professionals from various areas of the work world connected to the port environment. To this end, the theoretical contribution of the Mediterranean World definition by Fernand Braudel (1983/4) is accepted, for whom maritimity produces intricate networks of connection between the local and the global, in addition to contributions from Cultural History, from Roger Chartier (1989), for whom harmony and/or disagreements between practices and representations allow for approximations to the complexity experienced by the under-study subjects. Memory is used as a historical source of full value, as advocated by Marieta de Moraes Ferreira and Janaína Amado (2005). General bibliography of the state of Maranhão; intelectual production of chroniclers from the Baixada do Maranhão; Maranhão newspapers; and testimonies of professionals related to port activities in Raposa were used as crucial sources for this research.